Relationship between performance in youth category and success achievement in senior category in swimming - Krc, H.; Cillik, I.; Jelenák, P.; Odráška, L. (Journal of Human Sport & Exercise, 2021)
The aim of this study was to examine the relationship between youth and senior performance in swimming. The sample consisted of 49 men (age 21.24 ± 3.04) and 35 women (age 19.45 ± 2.13). The average FINA point score achieved for men was 632.71 ± 62.86 points. in women 645.62 ± 56.71 points. We included in our comparison performance of seniors achieved in a 25 m pool in 2019 season and their performance at the age of 12 for men and 11 years for women. The swimmers we monitored were ranked 1st to 50th in the Slovak Charts in 2019 season. The monitored disciplines were 50 m, 100 m, and 200 m freestyle. To assess the relationship between performance in the youth category and in the senior category we used the mathematical-statistical program IBM SPSS 23 and the nonparametric Spearman correlation coefficient for the ranking data. In the monitored disciplines we did not observe a statistically significant relationship between performance in the youth and senior categories in men or women. In 50 m freestyle men the values were: R = 0.279, p = .248. For women: R = 0.114 and p = .697. In 100 m freestyle men the values were: R = 0.218, p = .400. For women: R = 0.396 and p = .203. In 200 m freestyle men the values were: R = 0.091, p = .768. For women: R = 0.134 and p = .730.